2019
DOI: 10.1016/j.neuroimage.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow changes after a day of wake, sleep, and sleep deprivation

Abstract: Elucidating the neurobiological effects of sleep and wake is an important goal of the neurosciences. Whether and how human cerebral blood flow (CBF) changes during the sleep-wake cycle remain to be clarified. Based on the synaptic homeostasis hypothesis of sleep and wake, we hypothesized that a day of wake and a night of sleep deprivation would be associated with gray matter resting CBF (rCBF) increases and that sleep would be associated with rCBF decreases. Thirty-eight healthy adult males (age 22.1±2.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 72 publications
4
62
0
Order By: Relevance
“…Interestingly, the largest of these studies (Elvsåshagen et al, 2019) reported regional CBF increases related to duration of wakefulness in the same regions where we observed the strongest time of day-associated reductions in resting state BOLD signal fluctuation and RSFC (e.g. somatomotor and visual cortex).…”
Section: Potential Roles Of Homeostatic Mechanisms and Cerebral Bloodsupporting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, the largest of these studies (Elvsåshagen et al, 2019) reported regional CBF increases related to duration of wakefulness in the same regions where we observed the strongest time of day-associated reductions in resting state BOLD signal fluctuation and RSFC (e.g. somatomotor and visual cortex).…”
Section: Potential Roles Of Homeostatic Mechanisms and Cerebral Bloodsupporting
confidence: 51%
“…Based on the premise that synaptic strengthening has a significant metabolic cost (Harris et al, 2012), the synaptic homeostasis hypothesis (Tononi and Cirelli, 2003) predicts an increase in cerebral oxygen and glucose consumption, and as a result, increased cerebral blood flow (CBF) with cumulative wakefulness (Tononi and Cirelli, 2006). Indeed, several studies have reported elevated CBF in the evening relative to morning (Braun, 1997;Kuboyama et al, 1997;Elvsåshagen et al, 2019; but see Shannon et al, 2013;Hodkinson et al, 2014).…”
Section: Potential Roles Of Homeostatic Mechanisms and Cerebral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…We illustrate the ExploreASL image processing results and reproducibility for three populations with similar 2D-EPI PCASL protocols: perinatally-infected HIV children, healthy adults, and elderly with mild cognitive complaints, from the NOVICE (Blokhuis et al 2017), the Sleep (Elvsåshagen et al 2018), and the European Prevention of Alzheimer’s Dementia (EPAD) studies (Ritchie et al 2016), respectively (Supplementary Table 3). All three studies adhered to the Declaration of Helsinki and were approved by the local ethics committees (Academic Medical Center (AMC) in Amsterdam, Norwegian South East Regional Ethics Committee, and VU Medical Center Amsterdam and University of Edinburgh, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…ExploreASL allows to adjust for individual arterial blood T1 by either providing its value directly (Li et al 2017) or by providing the hematocrit value and computing the blood T1 (Hales et al 2016). As hematocrit and blood T1 measurements can be noisy - especially when obtained at different laboratories - a pragmatic approach is to apply the average blood T1 correction on a population rather than on an individual level (Elvsåshagen et al 2018). Additionally, hematocrit and blood T1 can be modeled based on age and sex (Hales et al 2014), but this requires validation.…”
Section: Theory: Implementationmentioning
confidence: 99%